Psychology of Children’s Cognitive toward Language Development - Ardiah Ningrum, Cucu (Lingual Journal of Language and Culture; Vol 3 No 1 (2017)DO - 10.24843/LJLC.2017.v03.i01.p08)
This paper aims to explain how the Cognitive Psychology supports the language development on children. The supporting data was taken from some related books and journals. The data collection is conducted through the proper source collection used for obtaining various information related to the topic. Then the information obtained from many sources was analyzed. The result of the analyses shows that the language acquisition process begins even since infancy period. In this process, the cognitive psychology supported it. In the process of acquiring the language, the children will pass through four steps of Cognitive process namely, sensorimotor stage, pre-operational stage, concrete operation stage, and formal operation stage. The entire stages are related to human’s age. In addition there are some assumptions of children’s cognitive development which are children’s schemas, assimilation, accommodation, and equilibration. Keywords: Cognitive, Cognitive Psychology, Language development